Relaxation study of pre-densified silica glasses under 2.5 MeV electron irradiation - Nadège Ollier (Nature Portfolio, 2019)
Abstract We examined the “relaxation properties” of pre-densified synthetic fused silica glass under 2.5 MeV electron irradiation. The densification of the glass was either obtained by hot compression (5 GPa-350 °C and 5 GPa-1000 °C) or via a thermal treatment increasing its fictive temperature (Tf = 1050, 1250 and 1400 °C). Under irradiation, the pre-densified silica glasses exhibit a relaxation of their macroscopic density with increasing integrated dose. Density was reduced for hot compressed silica and increased for Tf samples with different relaxation rates but it is remarkable that all sample densities follow a trend towards the same equilibrium value around 2.26 for a dose larger than 10 GGy despite a different final topology. After irradiation of hot compressed silica, the Raman spectra display a significant increment of 4 and almost 3-membered rings whereas they exhibit a glass density reduction; demonstrating that a D2 band increase cannot be considered as an absolute marker of the glass compaction. The correlation between density and D2 intensity remains valid until silica density remains lower than 2.26. In contrast, the FWHM of the main band peaking at 440 cm−1 appears to remain correlated to the silica glass density for all investigated samples.